If `(x^12 + x^3)/(x^6) = 0`, find `x^36 + 1/(x^36)`.
\[ \text { If } \frac{x^{12}+x^3}{x^6}=0, \text { find } x^{36}+\frac{1}{x^{36}} \]
Share
Lost your password? Please enter your email address. You will receive a link and will create a new password via email.
Please briefly explain why you feel this question should be reported.
Please briefly explain why you feel this answer should be reported.
Please briefly explain why you feel this user should be reported.
Given:
– The equation \(\frac{x^{12} + x^3}{x^6} = 0\).
1. Simplify the equation by dividing each term by \(x^6\):
\[ \frac{x^{12}}{x^6} + \frac{x^3}{x^6} = 0 \]
\[ x^6 + \frac{1}{x^3} = 0 \]
2. Rearrange the equation to express \(x^6\) in terms of \(x^3\):
\[ x^6 = -\frac{1}{x^3} \]
3. Raise both sides of the equation to the 3rd power to eliminate the fraction:
\[ (x^6)^3 = \left(-\frac{1}{x^3}\right)^3 \]
\[ x^{18} = -1 \]
4. Further, raise both sides to the 2nd power to find \(x^{36}\):
\[ (x^{18})^2 = (-1)^2 \]
\[ x^{36} = 1 \]
Conclusion:
– The value of \(x^{36}\) is 1.
– Therefore, \(x^{36} + \frac{1}{x^{36}} = 1 + 1 = 2\).